Experience and perception of utilizing virtual clinic in neurological assessment in Saudi Arabia - Mohammed Hmoud; Mohammed Hmoud; Mohammed Hmoud; Hassan K. Salamatullah; Hassan K. Salamatullah; Dania E. Faidah; Dania E. Faidah; Seraj Makkawi; Seraj Makkawi; Seraj Makkawi (Frontiers in Neurology, 2023)
IntroductionThe World Health Organization defined electronic health as “the unified usage of information technology and electronic communications in the health sector.” In the Kingdom of Saudi Arabia, outpatient encounters were largely shifted to virtual clinics due to the crisis caused by COVID-19. This study aimed to evaluate the neurology consultants', specialists', and residents' experience and perception of utilizing virtual services for neurological assessment in Saudi Arabia.MethodsThis cross-sectional study was conducted by sending an anonymous online survey to neurologists and neurology residents in Saudi Arabia. The survey was developed by the authors and contained three main sections: demographics, subspecialty and years of experience after residency, and virtual clinics during the coronavirus disease 2019 (COVID-19) pandemic.ResultA total of 108 neurology-practicing physicians in Saudi Arabia responded to the survey. Overall, 75% experienced virtual clinics, and 61% of them used phones for consultation. In neurology clinical practice, there was a significant difference (P < 0.001) regarding the teleconsultations for follow-up patients compared to the newly referred patients, being more suitable for the follow-up cases. Additionally, most neurology practicing physicians showed more confidence in performing history-taking tasks virtually (82.4%) than in physical examination. However, it was found that consultants were significantly (P < 0.03) more confident to virtually perform the cranial nerve, motor, coordination, and extrapyramidal assessments than the neurology residents. Physicians deemed it more suitable to conduct teleconsultations for patients with headaches and epilepsy than for those with neuromuscular and demyelinating diseases/multiple sclerosis. Furthermore, they agreed that patients' experiences (55.6%) and physicians' acceptance (55.6%) were the two main limitations to implementing virtual clinics.DiscussionThis study revealed that neurologists were more confident in performing history-taking in virtual clinics than in physical exams. On the contrary, consultants were more confident in handling the physical examination virtually than the neurology residents. Moreover, the most accepted clinics to be handled electronically were the headache and epilepsy clinics in comparison to the other subspecialties, being mainly diagnosed using history. Further studies with larger sample sizes are warranted to observe the level of confidence in performing different duties in neurology virtual clinics.